Pengaruh Implementasi SIMBG Terhadap Kepuasan Pelayanan Perizinan PBG Di Dinas PUPR Kota Cimahi - Ramdhan, Juanda; Miswan, Miswan; Suryaman, Warman (Jurnal Publisitas, 2023)
The aim of this research is to assess the impact of implementing the Building Management Information System (SIMBG) on the level of customer satisfaction in licensing at the Cimahi City PUPR Service. This research uses quantitative methods. Data was collected through the use of a questionnaire in the form of a Likert scale. The data was analyzed using descriptive statistics using a simple linear regression formula. The results of the assistance data are explained in the form of tables and narratives using SPSS software. Research findings show that the implementation of SIMBG has a significant influence on the level of customer satisfaction in the licensing process at the Cimahi City PUPR Service, namely around 89.7%. The remainder, around 10.3%, was influenced by other factors not examined in this study. Therefore, the hypothesis in this study can be accepted because it is supported by statistical significance.